The Perception of Doctor and Pharmacist in Interprofessional Collaborative in Pharmaceutical Care Services at General Hospital H. Adam Malik Medan - Wakidi, Riza Fahlevi; Nurpermatasari, Adhisty (Talenta Publisher, 2020)
Abstract. Collaboration is a complex process that requires planned knowledge sharing and be a joint responsibility to treat patients. The purpose of this study was to determine the perception of doctors and pharmacists in terms of the aspects of acceptance, expectations, and experience in collaborating on pharmaceutical care services on general hospital of H. Adam Malik Medan. This research is a survey research, located at general hospital of H. Adam Malik Medan. The sample in this study were 50 doctors and 10 pharmacists at general hospital of H. Adam Malik Medan. Data collection was carried out using a questionnaire. Analysis of the data used is descriptive analysis. The conclusion of this study is the perception of acceptance, current and future doctor's expectations of the role of pharmacists in collaborating on pharmaceutical care services is quite high, and perception of acceptance, pharmacist's current and future expectations of the role of pharmacists in collaborating on pharmaceutical care services are also high enough.